Sensation transference from plateware to food: The sounds and tastes of plates - Chen, Y; Woods, A; Spence, C (SAGE Publications, 2017)
Two experiments were designed to extend the well-known Bouba/Kiki effect to the case of an unusual set of commercially-produced plateware, and further to assess the influences of these plates on the expected taste of a dessert based on the theory of crossmodal correspondences. The results show that plates having a smoother circumference are more likely to be matched to “Bouba”, while those with a pointier circumference are more likely to be matched to “Kiki” instead, thus demonstrating the typical Bouba/Kiki effect.